Effect of Using Medial Arch Support on Foot Pain (Plantar Fasciitis) in Pregnant Women - Syaifuddin, Muhammad; Akbar, Muhammad Syaiful; Ariyani, Siska (Poltekkes Kemenkes Surakarta, 2025)
Background: Pregnancy often causes physical and psychological discomfort, including foot pain or plantar fasciitis due to inflammation of the plantar fascia, which is worsened by increased body weight. Medial arch support is an orthotic device designed to relieve this pain by stabilizing the medial longitudinal arch of the foot. This study aims to examine the effect of using medial arch support in reducing foot pain (plantar fasciitis) in third-trimester pregnant women. Methods: This quantitative study used a quasi-experiment with a one-group pre-test and post-test design to examine the effect of medial arch support on foot pain in pregnant women. The study was conducted in Noborejo, Salatiga. The sampling technique used is purposive sampling and involved 20 pregnant women who often complained of foot pain in the 2-3 trimesters. Pain levels were measured using the Numeric Rating Scale (NRS) before and after a two-week intervention with medial arch support. Results: The Wilcoxon test results indicate a significant reduction in foot pain (p= <0.001, p < 0.05). The average pain score before the intervention was 7.9, which decreased to 4.5 after the use of medial arch support, reflecting a pain reduction of 43%. The average difference in pain level before and after the intervention was 3.4. Conclusion: Medial arch support significantly reduces foot pain (plantar fasciitis) in pregnant women. This intervention offers a practical solution to reduce discomfort and improve the quality of health of pregnant women. Further studies are needed on the long-term use of medial arch support in pregnancy.